GLOBAL WARMING - Das Gupta, A B (Indian Science Cruiser, 2007)
Global warming is the generation of heat on the surface of the planet. It has been studied and analysed which lead to various human acÂtivities as well as geological factors. Investigation of cause and effect of global warming have been discussed with some concluding remarks in this article.